In silico; Linoleic acid and palmitic acid exerts antidiabetic effects by inhibiting protein tyrosine phosphatases associated with insulin resistance - Maha H.Al-Bahrani; Nada A.Kadhim; Raghad S. Mouhamad; Khlood Abedalelah Al-Khafaji (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objectives: The search for potential bioactive compounds for the discovery and development of targeted novel antidiabetic drugs is becoming more and more popular among scientists. So, the aim of this research is to find the inhibition activity of palmitic acid and linoleic acid extracted from Ballota saxatilis against protein tyrosine phosphatase (PTP: B1, N9 and 11) through simulation using molecular docking.Methods: Gas chromatography technique (GC) (Chrompack-Packard 438A) and a separation column type 30-SE with an inner diameter of 0.25 mm and a length of 30 m, was used to describe the biologically active chemicals found in Ballota saxatilis extracts.Results: Simulation technique gave the binding affinity, hydrogen bonding and the distances between ligand and its corresponding enzyme molecule. Molecular docking revealed that palmitic acid had strong binding affinities for PTP1B (-7.8) and PTP9 (-7.9) but had weaker affinities for PTP11 (up to (-7.4). α- Linoleic Acid (ALA) produced closely results of binding activity against PTP1B (-6.2) and PTP9 (-6.1) and lower binding activity reacted with PTP11. However, the ligand α- Linoleic acid could form hydrogen bonding beside other interactions with PTP1B, PTPN9 and PTPN11. The other ligand palmitic acid formed mainly hydrophobic interactions with the three enzymes. Only one hydrogen bond existed between ligand palmitic acid and the amino acid Lys260 located at PTPN11Conclusions: The extract of herb B. saxitalis could be applied by the researchers, and pharmaceutical companies around the world for inhibition of PTP1B, PTPN9 and PTPN11. These compounds may control diabetes with fewer side effects than conventional antidiabetic medications.